Reclaiming Cambodian History-The Case for a Truth Commission - Ramji, Jaya (Tufts Archival Research Center, 2005)
Volume 24, Issue 1. Spring Based on field interviews and analysis, Ramji advocates an international tribunal for the top leaders of the Khmer Rouge and a truth commission for lesser-ranting members as the most responsive method for healing Cambodian society.